The gut virome: a new microbiome component in health and disease - Cao, Zhirui; Sugimura, Naoki; Burgermeister, Elke; Ebert, Matthias; Zuo, Tao; Lan, Ping (EBioMedicine, 2022)
The human gastrointestinal tract harbours an abundance of viruses, collectively known as the gut virome. The gut virome is highly heterogeneous across populations and is linked to geography, ethnicity, diet, lifestyle, and urbanisation. The currently known function of the gut virome varies greatly across human populations, and much remains unknown. We review current literature on the human gut virome, and the intricate trans-kingdom interplay among gut viruses, bacteria, and the mammalian host underlying health and diseases. We summarise evidence on the use of the gut virome as diagnostic markers and a therapeutic target. We shed light on novel avenues of microbiome-inspired diagnosis and therapies. We also review pre-clinical and clinical studies on gut virome-rectification-based therapies, including faecal microbiota transplantation, faecal virome transplantation, and refined phage therapy. Our review suggests that future research effort should focus on unravelling the mechanisms exerted by gut viruses/phages in human pathophysiology, and on developing phage-prompted precision therapies.
Online verfügbar: 23 June 2022, Artikelversion: 23 June 2022
Gesehen am 20.11.2023